Autophagy and longevity: Evolutionary hints from hyper-longevous mammals - Locatelli, Andrea G.; Cenci, Simone (Frontiers in Endocrinology, 2022)
Autophagy is a fundamental multi-tasking adaptive cellular degradation and recycling strategy. Following its causal implication in age-related decline, autophagy is currently among the most broadly studied and challenged mechanisms within aging research. Thanks to these efforts, new cellular nodes interconnected with this phylogenetically ancestral pathway and unexpected roles of autophagy-associated genetic products are unveiled daily, yet the history of functional adaptations of autophagy along its evolutive trail is poorly understood and documented. Autophagy is traditionally studied in canonical and research-wise convenient model organisms such as yeast and mice. However, unconventional animal models endowed with extended longevity and exemption from age-related diseases offer a privileged perspective to inquire into the role of autophagy in the evolution of longevity. In this mini review we retrace the appearance and functions evolved by autophagy in eukaryotic cells and its protective contribution in the pathophysiology of aging.